Design and Synthesis of Porous Coordination Polymers with Expanded One‐Dimensional Channels and Strongly Lewis‐Acidic Sites. Issue 1 (23rd November 2017) - Kajiwara, Takashi; Higashimura, Hideyuki; Higuchi, Masakazu; Kitagawa, Susumu
Abstract: New porous coordination polymers (PCPs) consisting of La III cations and thiophene‐based tritopic organic linkers, La‐ThBTB andLa‐PhBTTc, are synthesized and structurally characterized. While these La‐PCPs exhibit the same type of one‐dimensional hexagonal channels, their thermal and chemical stability vary significantly with respect to each other, thus demonstrating the crucial importance of the design of the skeletal structure of the organic linker. Because of the large channel sizes and strong Lewis acidity of these La‐PCPs, the catalytic activity in the Lewis‐acid‐catalyzed cyanosilylation of carbonyl compounds shows among the highest reported so far for PCPs. Abstract : Porous coordination polymers (PCPs) consisting of La III cations and thiophene‐based tritopic organic linkers are synthesized and characterized. By using thiophene‐bridged benzenecarboxylates and benzene‐bridged thiophenecarboxylates, both linkers afford the same framework topology with one‐dimensional hexagonal channels, whereas the thermal and chemical stability of them differ significantly from each other. Both La‐PCPs show high activity in the Lewis‐acid‐catalyzed cyanosilylation.